Managing P2P Security. - Bailes, Jason E.; Templeton, Gary F. (Communications of the ACM, 2004)
It is informed that since its inception, the Internet has thrived on a myriad of innovative concepts and technologies. Recently, the peer-to-peer (P2P) architecture has evolved to empower masses of users to share a variety of file types, usually within a narrow niche such as music. There are many different applications of P2P, including file sharing, distributed computing, and real-time communication. In the P2P configuration, a computer becomes a node in a file-sharing network for users with common P2P applications. Using this scheme, a computer becomes a "peer" with simultaneous client and server roles. P2P protocols reduce the barriers to assigning a public network address to a peer, thus effectively creating a server within a client's name space. Each P2P network is defined by its client-side software, which uses its own unique set of protocols. P2P applications are designed to bypass the traditional Domain Name System (DNS) by retrofitting peers into the DNS model. As information technology departments are rewarded for their ability to preserve stability, P2P disrupts the traditional networking model and risks causing networking instability. With networks without servers being administered by unskilled users, many organizations are trying to keep this technology under control.